2008
DOI: 10.1002/ejlt.200700009
|View full text |Cite
|
Sign up to set email alerts
|

The use of electronic and human nose for monitoring rapeseed oil autoxidation

Abstract: This work was aimed at assessing the effectiveness of the electronic nose to monitor off-flavor associated with lipid oxidation as a supplementary tool to human sensory panel assessment. Therefore, correlations between electronic nose and sensory analysis were determined. Also GC analyses and chemical analyses of oil samples were run to characterize the analyzed samples with well-described parameters. Refined rapeseed oil was subjected to an accelerated storage test for 12 days at 60 7C and to an ambient tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 20 publications
(24 reference statements)
0
22
0
1
Order By: Relevance
“…The main aroma profile in lychee juice are alcohols and terpenoids, while the main volatiles in lychee wine are higher alcohols and esters (Alves et al, ; Chen, Yap, & Liu, ). Not all volatiles are odorants, and their impacts on flavor are related to their concentration and odor threshold (Mildner‐Szkudlarz, Jeleń, & Zawirska‐Wojtasiak, ). Ten key aroma compounds were selected based on the following (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…The main aroma profile in lychee juice are alcohols and terpenoids, while the main volatiles in lychee wine are higher alcohols and esters (Alves et al, ; Chen, Yap, & Liu, ). Not all volatiles are odorants, and their impacts on flavor are related to their concentration and odor threshold (Mildner‐Szkudlarz, Jeleń, & Zawirska‐Wojtasiak, ). Ten key aroma compounds were selected based on the following (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…This technique combines PLSR and DA. Thus, this process demonstrates the advantages of PLS, that is, feature extraction and noise reduction, and is applicable particularly in situations involving few samples but numerous variables [16]. The samples analyzed and the methods for data processing in PLS-DA were similar to those in PCA.…”
Section: Statistical Data Processingmentioning
confidence: 86%
“…Electronic nose (E‐nose) captures volatile compounds in the samples using a series of sensors to simulate artificial sensory . E‐nose has been used for detecting edible oil oxidation . Some preliminary studies have shown the ability of E‐nose to discriminate between oils characterized by different degrees of degradation due to a prolonged frying process and to predict the frying disposal time of sunflower oils used for frying in combination with fuzzy logic analyses …”
Section: Introductionmentioning
confidence: 99%